+0  
 
0
116
2
avatar

Let f(x) = 2x + 7 and g(x) = 3x + c. Find c if \((f \circ g)(x) = (g \circ f)(x)\) for all x.

Guest Jul 19, 2017
Sort: 

2+0 Answers

 #1
avatar+26366 
+2

We have:

 

 2(3x+c) + 7 = 3(2x+7) + c

 

6x + 2c + 7 = 6 x + 21 + c

 

2c + 7 = 21 + c

 

c = 14

 

.

Alan  Jul 19, 2017
 #2
avatar
0

Thank you!!

Guest Jul 19, 2017

11 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details